Bsx Is Essential for Differentiation of Multiple Neuromodulatory Cell Populations in the Secondary Prosencephalon - Schredelseker, Theresa (Front Neurosci, 2020)
The hypothalamus is characterized by great neuronal diversity, with many neuropeptides and other neuromodulators being expressed within its multiple anatomical domains. The regulatory networks directing hypothalamic development have been studied in detail, but, for many neuron types, control of differentiation is still not understood. The highly conserved Brain-specific homeobox (Bsx) transcription factor has previously been described in regulating Agrp and Npy expression in the hypothalamic arcuate nucleus (ARC) in mice. While Bsx is expressed in many more subregions of both tuberal and mamillary hypothalamus, the functions therein are not known. Using genetic analyses in zebrafish, we show that most bsx expression domains are dependent on Nkx2.1 and Nkx2.4 homeodomain transcription factors, while a subset depends on Otp. We show that the anatomical pattern of the ventral forebrain appears normal in bsx mutants, but that Bsx is necessary for the expression of many neuropeptide encoding genes, including agrp, penka, vip, trh, npb, and nts, in distinct hypothalamic anatomical domains. We also found Bsx to be critical for normal expression of two Crh family members, crhb and uts1, as well as crhbp, in the hypothalamus and the telencephalic septal region. Furthermore, we demonstrate a crucial role for Bsx in serotonergic, histaminergic and nitrergic neuron development in the hypothalamus. We conclude that Bsx is critical for the terminal differentiation of multiple neuromodulatory cell types in the forebrain.